Eksplorasi Teknik Tritik dengan Pewarna Teh pada Perancangan Tekstil Pakaian - astuti, dewi; Nurani Sulistyati, Apika (Hastagina : Jurnal Kriya Seni, 2024)
The tritik technique with geometric motifs has great potential to be developed, looking at the jumputan fabric motifs produced in the city of Surakarta, the majority of which are clove motifs, tumpal motifs and zig-zag motifs and do not use rules or provisions for stitch spacing. One of the efforts is to explore the tritik technique which produces geometric motifs using a combination of stitch techniques, baste folding techniques, and overcast stitch techniques by applying stitch spacing rules so that the geometric motifs produced are more optimal and consistent. The tritik techniques produced in the city of Surakarta are less diverse, so exploration of tritik techniques is needed to create more diverse motifs. The design of this work uses tea coloring from a certain brand which provides many variants. Different tea variants have a great opportunity to be developed as color variations because they create different colors with a stable consistency to enrich the natural coloring repertoire of tea. The design of this work is used as a clothing textile product for women of all ages. The design of this work uses the method of creating works of art by S.P Gustami which includes the exploration stage, design stage and realization stage. The result of this design is a clothing textile product using the tritik technique and tea dye. The tritik technique can be developed into geometric shapes such as lines, circles, hexagons, meanders and squares by using certain techniques and applying stitch spacing provisions